Mechanically Flexible Wireless Multisensor Platform for Human Physical Activity and Vitals Monitoring - Chuo, Y; Marzencki, M; Hung, B; Jaggernauth, C; Tavakolian, K; Lin, P; Kaminska, B (IEEE transactions on biomedical circuits and systems, 2010)
Practical usability of the majority of current wearable body sensor systems for multiple parameter physiological signal acquisition is limited by the multiple physical connections between sensors and the data-acquisition modules. In order to improve the user comfort and enable the use of these types of systems on active mobile subjects, we propose a wireless body sensor system that incorporates multiple sensors on a single node. This multisensor node includes signal acquisition, processing, and wireless data transmission fitted on multiple layers of a thin flexible substrate with a very small footprint. Considerations for design include size, form factor, reliable body attachment, good signal coupling, low power consumption, and user convenience. The prototype device measures 55 15 mm and is 3 mm thick. The unit is attached to the patient's chest, and is capable of performing simultaneous measurements of parameters, such as body motion, activity intensity, tilt, respiration, cardiac vibration, cardiac potential (ECG), heart rate, and body surface temperature. In this paper, we discuss the architecture of this system, including the multisensor hardware, the firmware, a mobile-phone receiver unit, and assembly of the first proof-of-concept prototype. Preliminary performance results on key elements of the system, such as power consumption, wireless range, algorithm efficiency, ECG signal quality for heart-rate calculations, as well as synchronous ECG and body activity signals are also presented.